Cooperative Legal Pluralism in Resolving Jarimah Khalwat Cases in Aceh - Tsania Miratush Sholichat; Achmad Gunaryo; Hamid Hanafi Hanan; Ishmah Auliya Salsabila (Universitas Islam Negeri Walisongo Semarang, 2026)
The study of the settlement of jarimah khalwat in Aceh generally separates the study of customary and formal sharia courts, so that cooperative interaction between systems is still poorly explored. This research is here to fill this gap through the framework of cooperative legal pluralism. This research is a type of normative legal research with a conceptual study approach. The analysis of the synchronization of norms between Qanun Jinayat and Qanun Pembinaan Kehidupan Adat shows the functional relationship between the Syar'iyah Court in ensuring legal certainty and the Gampong Court in maintaining social harmony. The main findings of the study offer a reconstruction model that prioritizes customary justice as an instrument of restorative justice. If the customary court fails, the settlement of the case is continued to the formal realm with customary decisions remaining a legal consideration in the Syar'iyah Court. This reconstruction contributes to normative integration that guarantees legal certainty, prevents double punishment, and still respects local wisdom of Aceh. Studi penyelesaian jarimah khalwat di Aceh umumnya memisahkan kajian peradilan adat dan syariat formal, sehingga interaksi kooperatif antar-sistem masih kurang tereksplorasi. Penelitian ini hadir untuk mengisi kekosongan tersebut melalui kerangka cooperative legal pluralism. Penelitian ini berjenis penelitian hukum normatif dengan pendekatan studi konseptual. Analisis sinkronisasi norma antara Qanun Jinayat dan Qanun Pembinaan Kehidupan Adat menunjukkan hubungan fungsional antara Mahkamah Syar’iyah dalam menjamin kepastian hukum dan Peradilan Gampong dalam menjaga harmoni sosial. Temuan utama penelitian menawarkan model rekonstruksi yang memprioritaskan peradilan adat sebagai instrumen keadilan restoratif. Jika peradilan adat gagal, penyelesaian perkara dilanjutkan ke ranah formal dengan keputusan adat tetap menjadi pertimbangan hukum di Mahkamah Syar’iyah. Rekonstruksi ini berkontribusi pada integrasi normatif yang menjamin kepastian hukum, mencegah hukuman ganda (double punishment), dan tetap menghargai kearifan lokal Aceh. Keywords: Legal Pluralism; Jarimah Khalwat; Aceh.